Analisis Nilai Perusahaan Menggunakan Model Tobins-Q untuk Menilai Kinerja Bank Rakyat Indonesia Tbk Periode 2013-2022 - Jamaludin (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim : This study aims to analyze the company value and financial performance of PT Bank Rakyat Indonesia Tbk. for the 2013–2022 period using Tobin’s Q and Return on Assets (ROA) indicators. Design/Methode/Approach : The research employs a quantitative descriptive approach by analyzing secondary data obtained from BRI’s annual financial statements. Tobin’s Q is calculated to measure market-based firm value, while ROA is used to assess financial performance and profitability. Research Finding : The results show that the Tobin’s Q ratio during 2013–2022 consistently exceeded one (Q > 1), indicating that BRI was in an overvalued condition, reflecting strong investor confidence and effective asset management. Meanwhile, the average ROA was 2.522%, categorized as very healthy according to Bank Indonesia standards, demonstrating the company’s consistent profitability despite a temporary decline in 2020 due to the COVID-19 pandemic. Theoretical contribution/Originality : This study strengthens empirical evidence that integrating market-based (Tobin’s Q) and accounting-based (ROA) indicators provides a more comprehensive assessment of firm performance. Practitionel/Policy implication : The findings suggest that BRI’s management should continue enhancing digital transformation, operational efficiency, and financial transparency to maintain long-term competitiveness. Research limitation : This study is limited to one state-owned bank; future research may compare multiple banks or add governance and risk management variables.